Virtual Laboratory of Unbalanced Transient Condition in Synchronous Generator - Sugiarto Kadiman; Arif Basuki; Diah Suwarti (Institute of Advanced Engineering and Science, 2017)
The electrical engineering department at the Sekolah Tinggi Teknologi Nasional (STTNAS), Yogyakarta has recently reconnoitered virtual laboratories for its undergraduate synchronous generator course to complement existing full-scale laboratory equipment. This study explores virtual laboratory development to be treated as an accessorial tool for enhancing instruction. The focus of this synchronous generator course is the dynamic transient behavior of the system after small disturbances as affected by the unbalanced load. The work is mainly carried out through nonlinear simulations under Matlab-Simulink. Results of the first version of the synchronous generator virtual laboratory and details of its development are provided.